Combined ultrasound–hydrothermal pretreatment enhances moisture diffusivity, energy efficiency, and quality retention during hot air drying of holy basil (Ocimum sanctum L.) - Pambudi, Suluh; Khamon, Duanghathai; Ngo, Tai Van; Saechua, Wanphut; Jongyingcharoen, Jiraporn Sripinyowanich (My University, 2026)
Drying of holy basil (Ocimum sanctum L.) is limited by slow internal moisture diffusion and severe degradation of heat-sensitive pigments and bioactive compounds during prolonged thermal exposure. This study investigates the combined effects of ultrasonic and hydrothermal pretreatments on moisture transport, energy efficiency, and quality retention during hot air drying at 60 °C. Ultrasonication (30 and 60 min), hot-water blanching, steam blanching, and their combinations were systematically evaluated through drying kinetics, effective moisture diffusivity (Deff), microstructural analysis, POD enzyme activity, specific energy consumption (SEC), and comprehensive quality assessment. Drying occurred entirely in the falling-rate regime, confirming diffusion-controlled moisture transport. The combined ultrasound–blanching treatment (US30B) exhibited the greatest changes in drying performance, enlarging stomatal openings and enhancing moisture transport during drying, which increased Deff nearly threefold (from 1.70 × 10−11 to 5.02 × 10−11 m2/s) and reduced drying time from 100 to 30 min. This transport intensification decreased total SEC by 11% while simultaneously minimizing shrinkage and enhancing rehydration capacity. Importantly, accelerated moisture removal may have reduced thermal and oxidative degradation, resulting in superior retention of chlorophyll, phenolics, flavonoids, and antioxidant activity (p ≤ 0.05), alongside improved green color stability. These findings suggest that pretreatment strategies that enhance internal moisture transport may improve both energy efficiency and functional quality in heat-sensitive leafy herbs. The combined ultrasound–hydrothermal pretreatment shows potential as a practical approach for improving drying performance and quality retention in herbal dehydration.
Keywords: Energy-efficient dehydration; Hydrothermal pretreatment; Pretreatment combination; Quality retention; Ultrasonic pretreatment